2006
DOI: 10.1111/j.1365-3083.2006.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐21 Induces T‐cell Activation and Proinflammatory Cytokine Secretion in Rheumatoid Arthritis

Abstract: Interleukin (IL)‐21 is a CD4+ T‐cell‐derived cytokine, which is involved in innate and adaptive immune response. In this study, we analysed IL‐21 receptor (IL‐21R) expression in peripheral blood and synovial fluid mononuclear cells, and investigated the role of IL‐21 in the induction of proinflammatory cytokine production by peripheral blood T cells (PB‐T) and synovial fluid T cells (SF‐T) from patients with rheumatoid arthritis (RA). Immunohistochemical staining demonstrated that IL‐21R‐positive cells were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 27 publications
(44 reference statements)
7
83
0
1
Order By: Relevance
“…Regarding the role of IL-21 in inflammatory forms of arthritis such as RA, studies in both mice and humans suggest that IL-21 might be involved in disease progression (29)(30)(31). Young et al demonstrated that blockade of IL-21 with the IL-21R-Fc fusion protein ameliorated clinical disease activity in animal models of inflammatory arthritis, suggesting that IL-21 contributes to the pathologic process of RA (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the role of IL-21 in inflammatory forms of arthritis such as RA, studies in both mice and humans suggest that IL-21 might be involved in disease progression (29)(30)(31). Young et al demonstrated that blockade of IL-21 with the IL-21R-Fc fusion protein ameliorated clinical disease activity in animal models of inflammatory arthritis, suggesting that IL-21 contributes to the pathologic process of RA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that blood and synovial fluid T cells from patients with RA produced higher levels of TNF␣ and interferon-␥ after stimulation with anti-CD3 and IL-21 than did T cells from patients with OA and healthy controls, suggesting that IL-21 contributes to the progression of RA by up-regulating the expression of proinflammatory cytokines (29). Therefore, it is conceivable that the IL-21-induced RANKL expression of CD4ϩ T cells might be partially mediated by the TNF␣ induced by IL-21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA peripheral blood and synovial T cells stimulated with anti-CD3 and IL-21 produce more TNF-a and interferon-g than T-cells from healthy controls. 37 Furthermore, inhibition of IL-21 results in reduced TNF-a production. 34 Taken together with evidence that IL-21 acts in an autocrine fashion upon human Th 17 cells in RA, 38 these data suggest that IL-21 makes a substantial contribution to the systemic inflammatory process in RA through upregulation of T-cell cytokines.…”
Section: à5mentioning
confidence: 99%
“…[8][9][10] The IL-21R can be upregulated on non-lymphoid tissues as well, suggesting a significant role for this cytokine in orchestrating many aspects of the inflammatory response. Increased expression of IL-21 and IL-21R have been associated with human rheumatoid arthritis, [11][12][13] lupus 14 and…”
Section: In Vitro Potency Pharmacokinetic Profiles and Pharmacologicmentioning
confidence: 99%